Ventilator-induced lung injury is mediated by the NLRP3 inflammasome - Kuipers, Maria T; Aslami, Hamid; Janczy, John R; van der Sluijs, Koenraad F; Vlaar, Alexander P J; Wolthuis, Esther K; Choi, Goda; Roelofs, Joris J T H; Flavell, Richard A; Sutterwala, Fayyaz S; Bresser, Paul; Leemans, Jaklien C; et al. (Anesthesiology (Philadelphia), 2012)
The innate immune response is important in ventilator-induced lung injury (VILI) but the exact pathways involved are not elucidated. The authors studied the role of the intracellular danger sensor NLRP3 inflammasome. NLRP3 inflammasome gene expression was analyzed in respiratory epithelial cells and alveolar macrophages obtained from ventilated patients (n = 40). In addition, wild-type and NLRP3 inflammasome deficient mice were randomized to low tidal volume (approximately 7.5 ml/kg) and high tidal volume (approximately 15 ml/kg) ventilation. The presence of uric acid in lung lavage, activation of caspase-1, and NLRP3 inflammasome gene expression in lung tissue were investigated. Moreover, mice were pretreated with interleukin-1 receptor antagonist, glibenclamide, or vehicle before start of mechanical ventilation. VILI endpoints were relative lung weights, total protein in lavage fluid, neutrophil influx, and pulmonary and systemic cytokine and chemokine concentrations. Data represent mean ± SD. Mechanical ventilation up-regulated messenger RNA expression levels of NLRP3 in alveolar macrophages (1.0 ± 0 vs. 1.70 ± 1.65, P less than 0.05). In mice, mechanical ventilation increased both NLRP3 and apoptosis-associated speck-like protein messenger RNA levels, respectively (1.08 ± 0.55 vs. 3.98 ± 2.89; P less than 0.001 and 0.95 ± 0.53 vs. 6.0 ± 3.55; P less than 0.001), activated caspase-1, and increased uric acid levels (6.36 ± 1.85 vs. 41.9 ± 32.0, P less than 0.001). NLRP3 inflammasome deficient mice displayed less VILI due to high tidal volume mechanical ventilation compared with wild-type mice. Furthermore, treatment with interleukin-1 receptor antagonist or glibenclamide reduced VILI. Mechanical ventilation induced a NLRP3 inflammasome dependent pulmonary inflammatory response. NLRP3 inflammasome deficiency partially protected mice from VILI.